Religion and the Identity of Independent Indonesia: A Study on Religious Narratives According to the Founding Fathers - Thaha, Idris; Ropi, Ismatu; Umam, Saiful (Ulumuna, 2024)
This article analyzes the speeches, works, and views of some Founding Fathers of Indonesia - Supomo, Muhammad Yamin, and Sukarno - as well as other key figures like Mohammad Hatta, K.H. Wahid Hasyim, Johannes Latuharhary, and Hoesein Djajadiningrat. It will explore their perspectives on the role of religion in Indonesia's political and social spheres. In Indonesia, where religion has significantly shaped the country's politics and society, politicians and elites largely agreed that religion is crucial to forming national identity. The main difference between nationalist and Islamist leaders was the extent of religion's influence on the new nation-state, not whether it had a role at all. Some argued for integrating faith into state affairs, while others favored separating the two. The enduring debate reflects the ongoing negotiation of competing visions of Indonesian nationhood, wherein religion is a significant axis of political and cultural expression. Moreover, the "religious state" concept encapsulates Indonesian leaders' nuanced approach to navigating the diverse religious landscape while maintaining a sense of national unity.